The association between a marker of oxidative stress in Saliva and severity of periodontal disease (Mustansiria Dental Journal, 2018)
Background: The aim of this study is to determine the relationship between the level of 8-hydroxydeoxyguanosine (8-OHdG) in saliva and severity of periodontal diseaseMaterial and method: Twenty five periodontitis patients were divided into two subgroups according to severity of periodontal disease (fifteen patients with probing pocket depth (PPD) 6mm). Clinical examination which included measurement of both PPD and bleeding on probing (BOP) were carried out before and after initial periodontal treatment in addition to assessment of 8-OHdG in saliva and gingival crevicular fluid (GCF).Result: Salivary level of 8-OHdG in those with PPD >6mm was higher than those with PPD6mm (mean PPD = 7.34) and only in some cases (4 out of 10).Conclusion: These data suggest that periodontally-involved teeth with deep pockets are a major source of salivary 8-OHdG levels may prove to be useful identifying patients with teeth of hopeless prognosis.